1986
DOI: 10.1126/science.232.4758.1620
|View full text |Cite
|
Sign up to set email alerts
|

Internal Mixture of Sea Salt, Silicates, and Excess Sulfate in Marine Aerosols

Abstract: Individual aerosol particles from the remote marine atmosphere were investigated by scanning electron microscopy and electron microprobe analysis. A large fraction of the silicate mineral component of the aerosol was found to be internally mixed with sea-salt aerosol particles. This observation explains the unexpected similarity in the size distributions of silicates and sea salt that has been observed in remote marine aerosols. Reentrainment of dust particles previously deposited onto the sea surface and coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
199
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(214 citation statements)
references
References 15 publications
11
199
0
4
Order By: Relevance
“…On the basis of our results, at a RH level of about 80%, the amount of water adsorbed is small compared to the dust particle size; consequently, the light-scattering properties of the dust are not appreciably affected. However, because of the coating of soluble material and the large size of the dust, the particles could become active cloud condensation nuclei at relatively low supersaturations [Andreae et al, 1986;Hobbs, 1993]. Finally, it should be noted that although mineral dust is a "natural" product, the mobilization of dust can be greatly affected by human activities especially in arid areas.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our results, at a RH level of about 80%, the amount of water adsorbed is small compared to the dust particle size; consequently, the light-scattering properties of the dust are not appreciably affected. However, because of the coating of soluble material and the large size of the dust, the particles could become active cloud condensation nuclei at relatively low supersaturations [Andreae et al, 1986;Hobbs, 1993]. Finally, it should be noted that although mineral dust is a "natural" product, the mobilization of dust can be greatly affected by human activities especially in arid areas.…”
Section: Discussionmentioning
confidence: 99%
“…These results obtained in the present study could also explain the enrichment of these ions in marine aerosols. [67] The presence of Br À in the subphase disordered the packing of the DPPC alkyl chains; i.e., it would lower the stability of organic films on an aerosol surface, resulting in defect sites in the DPPC monolayer. Experimental studies of water uptake by hydrophobic surfaces suggest that water uptake does indeed occur on these surfaces, preferentially at the defect sites.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Andreae et al (1986) reported that dust particles mixed internally with sea salt were collected in the atmosphere over the equatorial Pacific Ocean. Parungo et al (1986) collected some Saharan dust particles over the Atlantic Ocean containing a sea-salt component.…”
Section: Introductionmentioning
confidence: 99%